LITERATURE OF REVIEW THE INFLUENCE OF CONFLICT MANAGEMENT AND WORK ENVIRONMENT ON THE PERFORMANCE OF PT BLIBLI EXPRESS SERVICE (BES) EMPLOYEES - Fiqria Nur Ramadhan (Draf Solusi Indonesia, 2023)
This research is a literature study that examines therelationship between conflict management and workenvironment on performance. This research focuseson examining employee performance at PT BlibliExpress Service (BES). This research uses aquantitative method approach with a population ofPT Blibli Express Service (BES) employees.